Cultural Problems in an Expatriate's Work in Asian Countries - Przytuła, Sylwia (Problemy kulturowe w pracy ekspaty w krajach azjatyckich, 2010)
The success of expatriation is conditioned by numerous factors which merge and include: manager's personality factors (psychological features) which might predestine or disparage the person for work in international environment. Personality features are, according to the majority of psychologists, innate and difficult to be changed, however, they might be strengthened with the use of different trainings or courses, if they constitute an advantageous expatriate's side.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 173-185
Keywords: expatriate; triad model of management; Asian model of management; international cooperation